The art and history of books - Levarie, Norma (New Castle, DE : Oak Knoll Press ; London : British Library, 1995)
The Art and History of Books is a tightly written and lavishly illustrated panorama of book design from its earliest history to recent years. Tracing the history of fine books against a background of changing patrons, improving technology, religious and social change, and the state of the arts throughout the world, this volume encompasses both illustrated and unillustrated books with a breadth of detail not found in any other work. With 176 facsimile pages from books of unusual beauty or interest, many of them photographed especially for this volume, The Art and Histo ry of Books is more than a valuable reference source: it is a perfect example of expert design, cogent description, and relevant illustration.
-- Origins -- Greece -- Rome -- Byzantium -- Hiberno-Saxon Manuscripts -- Carolingian and Romanesque Manuscripts -- Gothic Manuscripts -- Renaissance Manuscripts -- The Beginning of Printing. Block Books. Gutenberg. Fust and Schoeffer -- The Fifteenth Century. Germany. Italy. France. The Netherlands. England. Spain -- The Sixteenth Century. Italy. Germany. France. The Netherlands. Spain. England -- The Seventeenth Century -- The Eighteenth Century -- The Nineteenth Century -- The Twentieth Century.
Originally published: New York : J.H. Heineman, 1968. With new foreword.
Includes bibliographical references and index.
Keywords: Books -- History; Printing -- History; Illustration of books; Books, Illustrated -- history; Printing -- history